Biarylmethoxy 2-nitroimidazooxazine antituberculosis agents: Effects of proximal ring substitution and linker reversal on metabolism and efficacy. Issue 18 (15th September 2015) - Thompson, Andrew M.; Blaser, Adrian; Palmer, Brian D.; Franzblau, Scott G.; Wan, Baojie; Wang, Yuehong; Ma, Zhenkun; Denny, William A.
Graphical abstract: Abstract: Certain biaryl analogues of antitubercular drug PA-824 displayed enhanced in vivo efficacies yet retained some susceptibility towards oxidative metabolism; therefore, two new strategies were explored to address this. Ortho -substitution of the proximal aryl ring with larger electron-withdrawing substituents maintained or improved compound stability but reduced aerobic potency; however, fluoro and cyano were well tolerated. In vivo, only 2′- or 3′-fluoro mono-substitution preserved high efficacy against acute infection, although one example was twofold more effective than delamanid against chronic infection. Reversal of the 6-oxymethylene linkage also permitted high potency and improved stability towards human liver microsomes, albeit, in vivo results were inferior. These novel findings provide further insight into the preferred structural features for lead candidates in this important drug class.